Identification of micro-plastics in Australian road dust. Issue 1 (February 2020) - Roychand, Rajeev; Pramanik, Biplob Kumar
Graphical abstract: Highlights: Very first study about the presence of micro-plastic in the Australian road dust. Samples were collected from two different locations of Metropolitan Melbourne. A large number of tyre wear-out particles were identified in the both samples. Abstract: The threat of micro-plastics in the marine environment is seriously being recognized worldwide for the dangers it is posing to not only the marine life and biodiversity but even to the human beings that form part of this food chain. The majority of these micro-plastics are considered to be generated from the wear-out of vehicle tyres. In Australia, there is a complete lack of scientific evidence to support the extent to which MPs are released from the road dust. Therefore, this study was undertaken to identify the presence of micro-plastics in Australian road dust and the results were validated using Fourier-transform infrared spectroscopy, scanning electron microscopy and energy dispersive x-ray spectroscopy material characterization techniques. The results clearly show the presence of a large number of tyre wear-out particles in small amounts of road dust samples collected from two separate suburban locations of metropolitan Melbourne area.